2017
DOI: 10.1080/10903127.2017.1325952
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Out-of-hospital Rapid Sequence Intubation of Non-Traumatic Brain Pathologies

Abstract: Non-traumatic brain pathologies are seven times more prevalent than traumatic brain injuries in patients that underwent out-of-hospital RSI in Victoria, Australia. Since the mechanisms through which RSI impacts mortality might differ between traumatic brain injuries and NTBP, and given that NTBP is very prevalent, it follows that the use of RSI in NTBP could be unsupported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…). The seven studies that were not suitable for prevalence‐of‐intubation pooling had cohorts that consisted entirely of those that were intubated, making a calculation of prevalence impossible . A comprehensive listing of the 46 articles with a description of study characteristics, prevalence‐bias assessment, and intubation prevalence are shown in Table S1 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…). The seven studies that were not suitable for prevalence‐of‐intubation pooling had cohorts that consisted entirely of those that were intubated, making a calculation of prevalence impossible . A comprehensive listing of the 46 articles with a description of study characteristics, prevalence‐bias assessment, and intubation prevalence are shown in Table S1 …”
Section: Resultsmentioning
confidence: 99%
“…Two studies provide survival estimates for ischaemic stroke: Petchy et al showed their ED and out‐of‐hospital intubation cohort had 16% survival and Santoli et al with 28% ED‐based survival, also with no comparison groups . A further two studies report survival outcomes for a heterogeneous group of non‐traumatic brain pathologies: Fouche et al demonstrated that their out‐of‐hospital RSI cohort had a 69% survival and Pakkanen et al showed a 65% intubation survival for the non‐traumatic brain pathologies in their out‐of‐hospital study …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations